Recovery of renal function after bilateral renal vein thrombo sis episode as complication of membranous glomerulopa thy: case report - Ximenes,Ana Larissa Pedrosa (2017)
ABSTRACT Renal vein thrombosis (RVT) is a complication often associated with nephrotic syndrome. It occurs due to a state of hypercoagulability common in the diseases that attend to this syndromic diagnosis. It should be suspected whenever there is nephrotic syndrome associated with sudden flank pain, hematuria and worsening of proteinuria. Bilateral RVT also presents with frequently oliguric renal dysfunction. This case reports a 33-year-old patient hospitalized for a nephrotic syndrome, with etiologic investigation suggestive of primary membranous glomerulopathy, which evolved with bilateral RVT associated with deterioration of renal function and need for renal replacement therapy. He promptly performed angiography with thrombectomy and thrombolysis, evolving with recovery of renal function in two weeks.